The effect of four soil water regimes on the performance of Barlinka table grapes in the Hexriver Valley - Fourie, Andre,1960- (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1989.